A Review of Component and Pharmacology Activities of Black Garlic - Novitaria Br Sembiring; Yoppi Iskandar (Majalah Obat Tradisional, 2019)
Black garlic is garlic fermented in high temperature and humidity, and the fermentation compound chemical in garlic changes to new chemicals, such as S-allyl cysteine (SAC), S-allylmercapto-cysteine, and arginine. The color changed to dark brown during the aging period because of the Maillard reaction, known as non-enzymatic browning reaction. Black garlic has 57.14% of fructose, 6.78% of glucose, and 7.62% of sucrose, which were mainly saccharides in black garlic to answer for its sweet taste. It is such a pharmacological activity which contains antioxidant, anti-cancer, hepatoprotective, can improve the immune system, reduce hyperglycemia, dyslipidemia, and anti-allergic. We summarize the current knowledge of a change in the components, bioactivity, production, and applications of black garlic, as well as the proposed future prospects on their possible applications as a functional pharmacy product.